Biochemical characterization of a GDP-mannose transporter from Chaetomium thermophilum - Premageetha, Gowtham Thambra Rajan (2023)
Nucleotide Sugar Transporters (NSTs) belong to the SLC35 family (human solute carrier) of membrane transport proteins and are crucial components of the glycosylation machinery. NSTs are localized in the ER and Golgi apparatus membranes, where they accumulate nucleotide sugars from the cytosol for subsequent polysaccharide biosynthesis. Loss of NST function impacts the glycosylation of cell surface molecules. Mutations in NSTs cause several developmental disorders, immune disorders, and increased susceptibility to infection. Atomic resolution structures of three NSTs have provided a blueprint for a detailed molecular interpretation of their biochemical properties. In this work, we have identified, cloned, and expressed 18 members of the SLC35 family from various eukaryotic organisms in Saccharomyces cerevisiae. Out of 18 clones, we determined Vrg4 from Chaetomium thermophilum (CtVrg4) is a GDP-mannose transporter with an enhanced melting point temperature (Tm) of 56.9̊C, which increases with the addition of substrates, GMP and GDP-mannose. In addition, we report—for the first time—that the CtVrg4 shows an affinity to bind to phosphatidylinositol lipids.